Organizational Structure Dynamics: Implications for Operational Effectiveness and Efficiency - Ahmad Husnul Khotimah; Rima Adistiawan Fitri (CAKRAWALA : Management Science Journal, 2025)
The requirements of a dynamic business environment necessitate modification to organizational structure. Operational efficacy and efficiency are significantly influenced by the dtnamics of organizational structure, which include centrelisation, formalization, and flexibility. The factors that influence both aspects are analtsed using a qualitative method that incorporates a literature rewiew and library research approach. The fidings indicate that the organizations responsiveness to chage is enhanced by a flexible structure, and digital technology and adaptive leadership are critical in facilitiatung decision-making and coordination. The organizations success influences operational efficiency. The significance of meticulous planning and comprehensive implementation in the management of organizational structure dynamics is underscored in this study to achive optimal performance.